The influence of various risk factors on the strength of pelvic floor muscle in women - Parezanović Ilić, Katarina; Mladenović Segedi, Ljiljana; Jurišić Škevin, Aleksandra; Živanović Mačužić, Ivana; Grbović, Vesna; Nurković, Jasmin S; Jovanović, Milan; Jeremić, Dejan (Vojnosanitetski pregled, 2017)
Background/Aim. Damage of any element of pelvic floor leads to its functional damages, reflected in the occurrence of urinary incontinence, prolapse of pelvic organs, fecal incontinence and sexual dysfunction. Basic aim of our paper was to investigate the influence of various risk factors on pelvic floor muscle strength in women. Methods. The study included 90 female patients and examined how age, job, body weight and height, number of deliveries, sports activities, incontinence occurrence, previous prolapse-caused gynecological surgeries, other gynecological surgeries and other conservatively treated gynecological diseases influence the value of pelvic floor muscle strength. Pelvic floor muscle strength was measured using vaginal dynamometer. Results. Univariate regression analysis showed that parameters such as age, demanding job, body height, number of deliveries, sports activities, prolapse-caused gynecological surgeries, other gynecological surgeries and other gynecological diseases were in positive correlation with the values of pelvic floor muscle strength. In multivariate regression model, incontinence and gynecological operation of prolapse were singled out as independent risk factors. Conclusion. If risk factors that cause damage to pelvic floor muscle are known, it is possible to prevent the damages and improve the quality of women’s life.